Kerugian Nasabah Akibat Kesalahan Pejabat Perbankan - Lambouw, Giovita Nathaza Prasedia; Laturette, Adonia Ivone; Latupono, Barzah (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Bank as financial institutions that provides financial services in doing their job and responsibility, also needed the community to run the wheels of the country’s economy by building relationships with the community as customers based on law and trust as a base of the relationship.Purpose of the Research: The purpose of this paper is to determine Bank’s responsible to the mistakes that caused by the bank official and the form of compensation that given by the Bank to the customer.Methods of the Research: The research method used is normative juridical research with analytical descriptive type through a conceptual approach, statuary approach and case studies.Results of the Research: Based on the results of the research: first, the relationship between the bank and the customer, apart from based by trust relationship, it also gives a legal responsibility by the bank. Second, parties that are proven to fulfilled the elements of unlawful act can be sued for compensation by the other party based on the amount of loss that they have caused and what kind of form of the compensation that must be replaced.